2018
DOI: 10.2298/vsp160510210s
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio in pediatric acute appendicitis

Abstract: Background/Aim. Acute appendicitis (AA) is the most frequent emergency and appendectomy is the most frequent abdominal operation in the pediatric surgery. Diagnosis of AA in children is more difficult due to a lack of cooperation and poor clinical history data, leading to significant number of misdiagnostic cases. Our aim was to explore whether neutrophil to lymphocyte ratio (NLR) may be useful in diagnosis and follow-up of AA in children. Methods. Prospective investigation of NLR values in 129 consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Some studies showed that NLR appears to have greater diagnostic accuracy than WBC [19]. In our previous publication we confirmed a faster activation of neutrophils and NLR increase, and delayed increase of CRP, in pediatric AA [20, 21]. Therefore usefulness of NLR in early diagnosis of AA is superior to CRP, but still not sufficiently reliable.…”
Section: Discussionmentioning
confidence: 72%
“…Some studies showed that NLR appears to have greater diagnostic accuracy than WBC [19]. In our previous publication we confirmed a faster activation of neutrophils and NLR increase, and delayed increase of CRP, in pediatric AA [20, 21]. Therefore usefulness of NLR in early diagnosis of AA is superior to CRP, but still not sufficiently reliable.…”
Section: Discussionmentioning
confidence: 72%
“…NLR was measured in three different time points with regard to surgery: preoperative, on day 1, and day 3 postoperatively. We demonstrated that NLR provides good monitoring of progression of AA in children and that its cutoff values may help in distinguishing the phases of AA; therefore, it could be used in diagnosis of AA in pediatric population [ 47 ]. In the literature available to us, we did not find any studies regarding MLR and PLR with repetitive measurements.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a significant correlation of MPXI neither with the overall PAS nor with the single parameters of this score, including the absolute number of leukocytes and the percentage of neutrophils. Additionaly, in our previous article we showed the lack of significant correlation between the MPXI and neutrophil-to-lymphocyte ratio (NLR) 22 .…”
Section: Discussionmentioning
confidence: 89%